Chemical Properties of Fish Gelatin from Skin and Bone of Yellowfin Tuna (Thunnus Albacares) - Seniwati; Syadza Firdausiah; Nur Madya; Meidistria Tandi Rapak (Hasanuddin University, 2021)
This study aims to extract and compare the chemical properties of gelatin from the skin and bone of yellowfin tuna (Thunnus albacares) by using the acid method. The proximate and FTIR analyses of tuna skin and bone gelatin (TSG and TBG) were conducted to determine their chemical properties. The acid condition successfully produced gelatin, which is 3.24% of TSG and 2.61% of TBG yields. The proximate properties revealed that both extracted gelatin BEG and CG fulfil the Indonesian standard quality of gelatin, with a high level of total protein and low lipid content. Amide A, I, II, and III were shown at 3452.58, 1637.56, 1517.98, and 1240.23 cm-1 respectively in TSG FTIR spectra, and at 3493.09, 1660.71, 1533.41, and 1238.30 cm-1, respectively in TBG spectra. Both skin and bone of yellowfin tuna can potentially be used in the production of gelatin for industrial and pharmaceutical purposes with further optimation.